Building Successful Mobile Services - Poikonen, Sari Marianne (My University, 2015)
The number of smartphone user’s has grown to the extent that companies have to address it in their services and products. Smartphones have also opened a direct connection to the consumer via mobile applications. Although the use of mobile phones is on the rise, companies still struggle to employ applications in a profitable way. The problem might lie in the misconception that one has to be present in mobile for the sake of mobile. In this case the ubiquitous nature of mobile doesn’t get the attention that it deserves. One of the ways to create deeper understanding of profitable mobile services is to look at the planning process and phases that go behind them. The research presents a suggested planning process derived from Strauss’s planning process for marketing strategies. After the model is presented the research takes a look at three mobile service cases from Wal-Mart, eBay and Amazon. The three case companies were stated to be the mobile winners of the year 2013. The cases concentrate on the tactics, mobile features, objectives, key principles and results of the mobile activities. All the cases employ the unique nature of the mobile device in a profitable way. Possible pitfalls of mobile activities are usually based the lack of knowledge in the possibilities that mobile devices provide. In this research the planning process is described as a chain of decisions and questions. The theoretical background opens the concepts on mobile marketing and which features of mobile marketing are seen as strategically important. The chain of phases for developing mobile services is derived from Strauss’s marketing planning process. The key factors that go into building mobile services are mobile drivers, mobile decision, strategic planning, mobile strategy, mobile tactics and analysis and reports. The planning process is tested with a Finnish banking company’s mobile application and then compared to the international cases. The case study showed that in order to get active users for the application, companies must address all the suggested phases and decisions that go into building a strategy. Important factors are proper strategic planning and establishing metrics that enable continuous improvements of the application.
Keywords: mobile service; mobile strategy; planning process; mobile application; mobile tactics.; fi=Markkinointi|en=Marketing|; fi=Markkinoinnin johtamisen maisteriohjelma|en=Master's Programme in Marketing Management|; fi=Digitaalinen media|en=Digital media|